Case Report: Efficacy of ofatumumab in refractory anti-NMDAR encephalitis: case series and literature review - Deng, Min; Xiong, Jing; Hu, Dan; Kong, Zhaohong; Li, Tao (Frontiers in Immunology, 2025)
Anti-NMDAR encephalitis is the most common autoimmune encephalitis. When first-line treatments fail, second-line therapies are employed. However, a standardized approach for second-line treatment has yet to be established. We presented three cases of anti-NMDAR encephalitis with seizures and psychosis as the primary symptom. These patients showed inadequate response to initial treatments, including intravenous immunoglobulin, methylprednisolone, and plasma exchange. However, their symptoms were effectively controlled following subcutaneous administration of ofatumumab. Previous studies have reported that twelve cases of anti-NMDAR encephalitis were effectively treated with ofatumumab. In this study, the modified Rankin scale (mRS) scores at the last follow-up for all fifteen patients (including our three cases) were significantly lower compared to scores at the peak of the disease (p < 0.001). Thirteen patients achieved full recovery. These findings suggest that CD20 monoclonal antibodies, particularly ofatumumab, may offer a promising treatment option for anti-NMDAR encephalitis.